Fibre reinforced recycled aggregate concrete: towards sustainable and resilient structures - Htet, Paing Min (Curtin University, 2024)
With construction and demolition waste increasing and raw materials such as natural aggregates depleting, using recycled coarse aggregates in concrete offers a sustainable solution. This thesis presents the development of recycled aggregate concrete mix incorporating fibres to enhance mechanical properties for structural applications. The developed fibre-reinforced recycled aggregate concrete can achieve performance comparable to or better than natural aggregate concrete under static and dynamic loads, at both material and structural levels.